Evaluating the vitamin requirements of wine-related yeasts and the resultant impact on population dynamics and fermentation kinetics - Julies, Jerobiam Marvin (Stellenbosch : Stellenbosch University, 2019)
Thesis (MScAgric)--Stellenbosch University, 2019.